Gender differences on oxidative stress markers and complement component C3 plasma values after an oral unsaturated fat load test - Ferri, Jordi; Navarro, Inmaculada; Alabadí, Blanca; Bosch-Sierra, Neus; Benito, Esther; Civera, Miguel; Ascaso, Juan F; Martinez-Hervas, Sergio; Real, Jose T (Clinica e investigacion en arteriosclerosis : publicacion oficial de la Sociedad Espanola de Arteriosclerosis, 2020)
Post-prandial lipaemia (PL), oxidative stress (OS), and complement component C3 (C3) values are related to the atherosclerosis process. The post-prandial response of C3 after an oral fat load test (OFLT) using unsaturated fat is poorly addressed. The aim of this study was to analyze and compare the post-prandial response of OS markers and C3 values in men and women after an OFLT using unsaturated fat. The study included a total of 22 healthy subjects with normal lipids and normal blood glucose (11 men and 11 pre-menopausal women). An oral unsaturated fat load test (OFLT: 50g fat per m body surface) was performed using a commercial liquid preparation of long chain triglycerides (Supracal®). OS markers and C3 were measured using standardized methods at fasting state and every 2h up to 8h after the OFLT. Men showed statistically significant higher C3, oxidized glutathione (GSSG), and oxidized-reduced glutathione (GSSG/GSH) ratio values at fasting state compared to that obtained in women. In addition, post-prandial C3 values and GSSG/GSH ratios were significantly higher in men compared to women. The GSSG value and GSSG/GSH ratio significantly decreased in men after the OFLT compared to fasting values. In contrast, the post-prandial OS markers decrease observed in women was not statistically significant. In fasting state, men showed higher statistically significant C3 values and OS markers than women. The post-prandial OS markers (GSSG and GSSG/GSH ratio) significantly decrease after the OFLT with unsaturated fat in men compared to women.